2008
DOI: 10.1063/1.2905765
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic anisotropy revealed by NMR double pulsed field gradient experiments with arbitrary timing parameters

Abstract: We consider a general double pulsed field gradient experiment with arbitrary experimental parameters and calculate an exact expression for the NMR signal attenuation from restricted geometries, which is valid at long wavelengths, i.e., when the product of the gyromagnetic ratio of the spins, the pulsed gradients' duration, and their magnitude is small compared to the reciprocal of the pore size. It is possible to observe microscopic anisotropy within the pore space induced by the boundaries of the pore, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
208
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 128 publications
(216 citation statements)
references
References 27 publications
8
208
0
Order By: Relevance
“…Note that the eigenfunctions, u k ͑r͒, are the same functions used in the eigenfunction expansion of the diffusion propagator whose long time asymptotic demands one of the eigenvalues to vanish. 22 If this eigenvalue is assigned the index 0, i.e., 0 = 0, then u 0 ͑r͒ = V −1/2 , where V denotes the pore volume.…”
Section: A Brief Review Of the Mcf Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that the eigenfunctions, u k ͑r͒, are the same functions used in the eigenfunction expansion of the diffusion propagator whose long time asymptotic demands one of the eigenvalues to vanish. 22 If this eigenvalue is assigned the index 0, i.e., 0 = 0, then u 0 ͑r͒ = V −1/2 , where V denotes the pore volume.…”
Section: A Brief Review Of the Mcf Frameworkmentioning
confidence: 99%
“…Experiments performed on well-controlled NMR phantoms consisting of cylindrical tubes suggested that the predictions of Ref. 22 can be employed to obtain accurate estimates of small compartmental dimensions. 23 In a different study, it was predicted that when all gradient orientations were kept parallel to each other in a multi-PFG acquisition with an even number of gradient pulse pairs, increasing the gradient strength would yield peculiar features such as zero crossings that are robust to the heterogeneity of the specimen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Computer simulations [13,14] corroborated that at parallel diffusion gradients a decrease in signal is expected when increasing due to the decreasing restriction effect described by Mitra [2,15].…”
Section: Introductionmentioning
confidence: 59%
“…Recent advances in the analytical description of the diffusion MRI signal [14], as well as its numerical prediction [15,16], make it now conceivable to study and optimize the sensitivity of this experimental protocol. Previous work [17] has shown that the parallelantiparallel difference in signal attenuation in DDE decays exponentially with an increase of delay between diffusion encodings -the mixing time (τ m ).…”
Section: Introductionmentioning
confidence: 99%